Flypaper effect pada belanja daerah kabupaten/kota di Provinsi Jambi - Elfira Rahma Dayanti; Arman Delis; Emilia Emilia (Konsentrasi Pembangunan Regional dan Publik, Prodi Ekonomi Pembangunan, Fakultas Ekonomi dan Bisnis, Universitas Jambi, 2018)
This research aims to analyze: 1) the contribution and growth of PAD, and the role of balancing fund in financing the regional expenditure of district/city in Jambi Province; 2) the influence of General Allocation Fund (DAU), Revenue-Sharing Fund (DBH), and Own Source Revenue (PAD) to the Regional Expenditure and to detects the flypaper effect. The analytical method used is descriptive and quantitative research methods using Estimates done by using pooled data regression. The analysis showed that the contribution and growth of PAD is still relatively low, and equalization fund had a higher contribution in financing regional expenditure. Simultaneously DAU, DBH, and PAD have a significant influence on regional expenditure. Partially, only DAU and PAD have a significant effect, while DBH has no significant effect on regional expenditure. Furthermore, the flypaper are not detected on regional expenditure district/city in Jambi Province